The application of the Mahlangu case on the COIDA and other safety legislation: A legal analysis - Van der Bank, Marjone; Karsten, Jaco (International Journal of Occupational Safety and Health, 2024)
The Compensation for Occupational Injuries and Diseases Act 139 of 1993 (hence COIDA) provides for the compensation of any disablement caused by an occupational injury or disease that an employee sustains or contracts in the course of employment. This inter alia includes the death of an employee that resulted from an occupational injury or disease. Until recently, domestic workers in South Africa have been excluded from COIDA. In Mahlangu and Another v Minister of Labor and Others the Constitutional Court considered the present-day exclusion of domestic workers in South Africa from social security benefits associated with occupational injuries and diseases, notwithstanding other workers benefitting from comparable social benefits. The article therefore presents an overview of how the judgement in the Mahlangu-case stands to impact on the lives of domestic workers involved in workplace incidents. In light of the judgement, the authors reviewed the current legal framework associated with workplace injury claims and considered how the judgment stands to develop the legal framework and contribute towards social benefits of domestic workers. The importance of the judgment must therefore be considered against the background that the judgment confirms and assess the rights of domestic workers whereby they too must be able claim compensation in terms of COIDA. The authors also provide further insight into the significance of the invalidity of section1 (xix) (v) of COIDA and why the exclusion of domestic workers in terms of COIDA cannot be justified. This paper will examine and analyze the impact and relationship of the Mahlangu-case on legislation.